Time to Detection of Hepatitis C Virus Infection With the Xpert HCV Viral Load Fingerstick Point-of-Care Assay: Facilitating a More Rapid Time to Diagnosis. (29th January 2020) - Grebely, Jason; Catlett, Beth; Jayasinghe, Indika; Valerio, Heather; Hajarizadeh, Behzad; Verich, Andrey; Cunningham, Philip; Martinello, Marianne; Tillakeratne, Shane; Silk, David; Dore, Gregory J; Applegate, Tanya L
Abstract: Background: Xpert HCV Viral Load Fingerstick assay (Xpert HCV VL FS) is a point-of-care test quantifying HCV RNA in <1 hour, enabling same-visit diagnosis and treatment. Methods: This study evaluated time to HCV RNA detection using the Xpert HCV VL FS assay. Fingerstick whole-blood samples were collected from participants in an observational cohort in Australia. Results: In May 2018–2019, 1468 participants were enrolled, 1426 had Xpert HCV VL FS testing performed, and 1386 had a valid result. HCV RNA was detected in 23% (325/1386). Among people with undetectable HCV RNA (n = 1061), median time to result was 57 minutes. Among people with detectable HCV RNA (n = 325), median time to HCV RNA detection was 32 minutes and 80% (261/325) had a detectable HCV RNA result in ≤40 minutes. Median time to HCV RNA detection was dependent on HCV RNA level. Conclusions: A quicker HCV diagnosis could be achieved by monitoring the time when HCV RNA is first detected with the Xpert HCV VL FS test, rather than HCV RNA quantification, although the current platform does not allow for this. These findings could facilitate new strategies to reduce waiting times for an HCV diagnosis and improve linkage to treatment. Abstract : Among people with detectable HCV RNA, median time to HCV RNA detection was 32 minutes with the Xpert HCV VL FS test. New strategies to reduce time to detection could reduce waiting times for HCV diagnosis, improving linkage to treatment.